Matrix metalloproteinase-7 in periodontitis with type 2 diabetes mellitus - F. Zeidán‐Chuliá; D. Yilmaz; L. Häkkinen; E. Könönen; B.‐H. Neves de Oliveira; G. Güncü; V.‐J. Uitto; F. Caglayan; U. K. Gürsoy (Blackwell Munksgaard, 2022)
Background and Objective: Elevated levels of matrix metalloproteinase‐7 (MMP7) have been observed in serum samples of subjects with type 2 diabetes mellitus (T2DM) and in gingival tissues of subjects with periodontitis. The aim of the present study was to collect in vivo and in silico evidence on the role of MMP7 in the interplay between T2DM and generalized periodontitis (GP).
Material and Methods: The extent of MMP7 expression and localization were immunohistochemically analyzed in gingival tissues of patients with GP with T2DM (T2DM/GP, n = 11), systemically healthy patients with GP (n = 7), and systemically and periodontally healthy controls (n = 11). An in silico network model was built to determine the interactions between MMP7 and T2DM pathways. Regulation of neutrophil transmigration by MMP7 was analyzed in a knock‐out mice model.
Results: In human gingival tissues, the proportion of cells with robust MMP7 expression was elevated in patients with T2DM/GP in comparison to controls (P = .014). According to the in silico analysis, “hydroxyl radical” and “hydrogen peroxide” compounds were among the most central nodes of the network, and were within the shortest paths connecting “glucose” to “MMP7.” In MMP7 knock‐out mice, an intense accumulation of neutrophils was observed in the gingival epithelium as compared to wild‐type mice (P = .0001).
Conclusion: Elevated MMP7 expression in gingival tissues of patients with T2DM/GP is related to the activation of reactive oxygen species by hyperglycemia. Suppression of MMP7 expression results in impaired neutrophil transmigration in gingiva.